Healthcare associated infective endocarditis by incredibly aggressive Staphylococcus lugdunensis - Ibrahim, Rosni; Awang Hamat, Rukman; Rohaizat, Shahidatulnadia; Amir, Amira (Universiti Putra Malaysia, 2024)
A man in his 50s with underlying end stage renal failure presented with fever for one day and unconsciousness. Transthoracic echocardiogram showed large regurgitation over anterior mitral valve suggestive of infective endocarditis. Three sets of blood culture grew S. lugdunensis. He was started on intravenous cloxacillin 2g six hourly. Patient’s condition did not improve despite optimum therapy given. He died after twenty days of treatment due to septic shock secondary to mitral valve IE with septic encephalopathy. S. lugdunensis is an aggressive pathogen causing destructive IE in immunocompromised patients. Infection begins with colonization of the internal jugular vein catheter resulting in bacteremia. Matrix-assisted laser desorption/ionization–time-of-flight mass spectrometer (MALDI-TOF) reduces the timing of pathogen identification thus allowing early initiation of antimicrobial therapy. Appropriate antibiotic therapy reduces mortality however he died due to severe complications of sepsis and encephalopathy.